2023
DOI: 10.3389/fpls.2023.1044675
|View full text |Cite
|
Sign up to set email alerts
|

Plant production of a virus-like particle-based vaccine candidate against porcine reproductive and respiratory syndrome

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a disease leading to spontaneous abortions and stillbirths in sows and lowered life quality and expectancy in growing pigs. PRRS is prevalent worldwide and has significant economic impacts to swine industries around the globe. Co-expression of the two most abundant proteins in the viral envelope, the matrix protein (M) and glycosylated protein 5 (GP5), can produce a neutralizing immune response for the virus providing a potentially effective subunit vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Depending on the protein’s stability, conformation, and post-translational modifications, some proteins will become more or less abundant over the first week or two before they disappear completely. Some proteins remain stable over 3-8 days ( Chin-Fatt et al., 2021 ; VanderBurgt et al., 2023 ), some increase their accumulation with time ( Saberianfar et al., 2019 ), and others reach their highest accumulation at 4-6 days and then go down with time ( Garabagi et al., 2012 ). Here, we found that accumulation levels are highest four days post-infiltration, and this is the time we subsequently harvested the infiltrated leaf material.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the protein’s stability, conformation, and post-translational modifications, some proteins will become more or less abundant over the first week or two before they disappear completely. Some proteins remain stable over 3-8 days ( Chin-Fatt et al., 2021 ; VanderBurgt et al., 2023 ), some increase their accumulation with time ( Saberianfar et al., 2019 ), and others reach their highest accumulation at 4-6 days and then go down with time ( Garabagi et al., 2012 ). Here, we found that accumulation levels are highest four days post-infiltration, and this is the time we subsequently harvested the infiltrated leaf material.…”
Section: Resultsmentioning
confidence: 99%